2020
DOI: 10.31235/osf.io/zqmwa
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Applications of GIS and Geospatial analyses in COVID-19 research: A systematic review

Abstract: Geographic Information Science (GIS) had established itself as a distinct domain and incredibly useful whenever the research is related to geography, space, and other spatio-temporal dimensions. However, the scientific landscape on the integration of GIS in the COVID related studies is largely unknown. In this systematic review, we assessed the current evidence on the implementation of GIS and other geospatial tools and technologies in COVID-19 pandemic. We systematically retrieved and reviewed 79 research art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

7
1

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…While some of the low-and middle-income countries (LMICs) such as Brazil, Mexico, China, South Africa, and India are engaged in syndemics research, their individual and collective contributions appeared to be limited, which informs a critical research gap in LMICs. This is consistent with previous research that reported a low scholarly output from LMICs in different areas of health sciences [45][46][47][48]. In the case of syndemics research, the historical and persistent gaps in research capacities in LMICs are likely to be compounded by the fact that syndemics have been primarily conceptualized and extensively studied by scholars and institutions in high-income countries.…”
Section: Discussionsupporting
confidence: 90%
“…While some of the low-and middle-income countries (LMICs) such as Brazil, Mexico, China, South Africa, and India are engaged in syndemics research, their individual and collective contributions appeared to be limited, which informs a critical research gap in LMICs. This is consistent with previous research that reported a low scholarly output from LMICs in different areas of health sciences [45][46][47][48]. In the case of syndemics research, the historical and persistent gaps in research capacities in LMICs are likely to be compounded by the fact that syndemics have been primarily conceptualized and extensively studied by scholars and institutions in high-income countries.…”
Section: Discussionsupporting
confidence: 90%
“…Evidence from Vietnam and Philippines inform that the prevalence of mental health problems may range from 3.4% to 28.8% [ 85 , 86 ]. The variations of psychosocial burden of this pandemic requires a consideration of spatial attributes of mental health problems as well as psychosocial dynamics in different phases of the pandemic in respective contexts [ 87 , 88 ]. Our review found a comparatively higher prevalence through a quantitative synthesis of 35 studies with samples representing healthcare providers as well as the general population in South Asia, which necessitates further research to elucidate the psychosocial impacts of COVID-19 in South Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…Such segments of individuals with specific digital behavior may require personalized interventions for preventing unhealthy screen use. Additionally, place and population-specific limitations and opportunities for digital health technologies should be explored for optimal implementation of such intervention 49,50 . Strategies such as setting limits for screen-based educational or institutional activities complemented by planned exercises that involve offline communications and activities can be useful for people staying at home and attending online sessions 51 .…”
Section: Mitigating Adverse Health Outcomes Associated With Screen Timentioning
confidence: 99%